Myocardial energetics is not compromised during compensated hypertrophy in the Dahl salt-sensitive rat model of hypertension - Tran, Kenneth (Am J Physiol Heart Circ Physiol, 2016)
Salt-induced hypertension leads to development of left ventricular hypertrophy in the Dahl salt-sensitive (Dahl/SS) rat. Before progression to left ventricular failure, the heart initially undergoes a compensated hypertrophic response. We hypothesized that changes in myocardial energetics may be an early indicator of transition to failure. Dahl/SS rats and their salt-resistant consomic controls (SS-13(BN)) were placed on either a low- or high-salt diet to generate four cohorts: Dahl-SS rats on a low- (Dahl-LS) or high-salt diet (Dahl-HS), and SS-13(BN) rats on a low- (SSBN-LS) or high-salt diet (SSBN-HS). We isolated left ventricular trabeculae and characterized their mechanoenergetic performance. Our results show, at most, modest effects of salt-induced compensated hypertrophy on myocardial energetics. We found that the Dahl-HS cohort had a higher work-loop heat of activation (estimated from the intercept of the heat vs. relative afterload relationship generated from work-loop contractions) relative to the SSBN-HS cohort and a higher economy of contraction (inverse of the slope of the heat vs. active stress relation) relative to the Dahl-LS cohort. The maximum extent of shortening and maximum shortening velocity of the Dahl/SS groups were higher than those of the SS-13(BN) groups. Despite these differences, no significant effect of salt-induced hypertension was observed for either peak work output or peak mechanical efficiency during compensated hypertrophy.